2020
DOI: 10.1186/s12989-020-00351-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated polycyclic aromatic hydrocarbons from ambient particulate matter induce electrophysiological instability in cardiomyocytes

Abstract: Background: Epidemiologic studies have suggested that elevated concentrations of particulate matter (PM) are strongly associated with an increased risk of developing cardiovascular diseases, including arrhythmia. However, the cellular and molecular mechanisms by which PM exposure causes arrhythmia and the component that is mainly responsible for this adverse effect remains to be established. In this study, the arrhythmogenicity of mobilized organic matter from two different types of PM collected during summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…We have previously reported that ambient PM generates a substantial amount of ROS, which may induce electrophysiological instability in cardiomyocytes [20]. In addition, we revealed that this effect might be caused by PAHs, the main component of PM.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…We have previously reported that ambient PM generates a substantial amount of ROS, which may induce electrophysiological instability in cardiomyocytes [20]. In addition, we revealed that this effect might be caused by PAHs, the main component of PM.…”
Section: Discussionmentioning
confidence: 62%
“…In particular, there is convincing evidence to suggest that Fe generates ROS through the Haber-Weiss and Fenton reaction [51]. Indeed, we observed that ambient PM contained these metallic compounds in our previous study [20]. Therefore, further investigation of the association between metals and PAHs that lead to ROSmediated VSMC migration is needed.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations